2020
DOI: 10.2147/copd.s275002
|View full text |Cite
|
Sign up to set email alerts
|

<p>Information Needs in COPD After an Educational Programme: Influence in Exacerbations and Admissions</p>

Abstract: Introduction Improving patients’ information needs (IN) may contribute to better control in COPD. This study analyses IN using Lung Information Needs Questionnaire (LINQ) following an educational intervention, evaluates how clinical characteristics modify IN, and studies high IN as a prognostic factor for COPD exacerbations and hospital admissions. Methods Cohort of 143 patients with initial diagnosis of COPD included in a structured educational program. Two months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…In line with our findings, two other studies have found an association between patient education via pulmonary rehabilitation and reduced information needs (lowered LINQ scores) [ 21 , 30 ]. Unlike our study, however, neither of the previous studies observed associations between patient’s possibly changed health and exacerbation status and subjective needs for information.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our findings, two other studies have found an association between patient education via pulmonary rehabilitation and reduced information needs (lowered LINQ scores) [ 21 , 30 ]. Unlike our study, however, neither of the previous studies observed associations between patient’s possibly changed health and exacerbation status and subjective needs for information.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our ndings, the U.K. research group that developed the LINQ found an association between patient education via pulmonary rehabilitation and reduced information needs (the LINQ scores) (16). A 2020 study from Spain observed patients' posteducational LINQ scores similar to those found by the U.K. group (29). The patterns of information needs found in both of those studies were similar to the patterns in our study population.…”
Section: Main Ndingssupporting
confidence: 87%
“…The prevalence of COPD patients with an inadequate health literacy in Spain has been estimated at 58%, a quality which, if deficient, has been associated with unfavorable patient reported outcomes regarding dyspnea, wellbeing and daily life, and health-related quality of life; a higher risk of having comorbidities, need of caregiving, anxiety and depression, admissions or visits to the emergency department, and mortality. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%